Abu Bakar and the Conspiracy to Revive the Ancient Empire: Searching for Legitimacy in Johor-Pahang Relations - A Rahman Tang Abdullah (Department of History, Faculty of Social Sciences, Universitas Negeri Semarang, 2023)
This article examines Abu Bakar’s involvement in other Malay states regarding the relations between Johor and Pahang in the 19th century. It argues that his ultimate aim was to consolidate his position in Johor’s territory and obtain recognition from other Malay rulers. This is because the existing view claims that Abu Bakar had the ambition to restore the ancient empire of Johor-Riau-Lingga under his hegemony. Indeed, this view is generalised by historians even though it remains merely speculative. Thus, the discussion here is to provide a conclusive argument that rejects this view by showing that his involvement in other Malay states' political affairs was to consolidate his position in Johor.